Moğollar’ın Yakındoğu Politikası ve İSmâilîler’in Akıbeti Üzerine Bazı Bilgiler - Yuvalı, Abdülkadir (Atatürk Kültür Merkezi Başkanlığı, 1988)
[Abstract Not Available]
Some Notes on the Middle Eastem Policy of the Mongols and the Fate of the Ismailids